Travel Time Tomography to Delineate 3-D Regional Seismic Velocity Structure in the Banyumas Basin, Central Java, Indonesia, Using Dense Borehole Seismographic Stations - Hidayat, Hidayat; Nugraha, Andri Dian; Priyono, Awali; Marjiyono, Marjiyono; Setiawan, Januar H.; Sahara, David P.; Winardhi, Sonny; Zulfakriza, Zulfakriza; Rosalia, Shindy; Lelono, Eko B.; Permana, Asep K.; Setiawan, Ahmad (Frontiers in Earth Science, 2021)
The Banyumas Basin is a tertiary sedimentary basin located in southern Central Java, Indonesia. Due to the presence of volcanic deposits, 2-D seismic reflection methods cannot provide a good estimation of the sediment thickness and the subsurface geology structure in this area. In this study, the passive seismic tomography (PST) method was applied to image the 3-D subsurface Vp, Vs, and Vp/Vs ratio. We used 70 seismograph borehole stations with a recording duration of 177 days. A total of 354 events with 9, 370 P and 9, 368 S phases were used as input for tomographic inversion. The checkshot data of a 4, 400-meter deep exploration well (Jati-1) located within the seismic network were used to constrain the shallow crustal layer of the initial 1-D velocity model. The model resolution of the tomographic inversions was assessed using the checkerboard resolution test (CRT), the diagonal resolution element (DRE), and the derivative weight sum (DWS). Using the obtained Vp, Vs, and Vp/Vs ratio, we were able to sharpen details of the geological structures within the basin from previous geological studies, and a fault could be well-imaged at a depth of 4 km. We interpreted this as the main dextral strike-slip fault that controls the pull apart process of the Banyumas Basin. The thickness of the sediment layers, as well as its layering, were also could be well determined. We found prominent features of the velocity contrast that aligned very well with the boundary between the Halang and Rambatan formations as observed in the Jati-1 well data. Furthermore, an anticline structure, which is a potential structural trap for the petroleum system in the Banyumas Basin, was also well imaged. This was made possible due to the dense borehole seismographic stations which were deployed in the study area.